PENGEMBANGAN PROGRAM BIMBINGAN DAN KONSELING KOMPREHENSIF DALAM MENDUKUNG SDM UNGGUL DI SEKOLAH - Nugroho, Djoko; Saiful Muktiali; Nenda; Muhammad Cholid Abdurrohman; Putri Aneliya Marsya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the fragmented and insufficiently integrated implementation of school guidance and counseling programs, which has limited the development of students’ academic, personal, social, and career potential. The study aims to analyze the current implementation of guidance and counseling programs, develop a comprehensive model based on students’ needs, and examine its effectiveness in supporting the development of competent, adaptive, and well-characterized human resources. The study employs a Research and Development (R&D) method consisting of needs analysis, program design, expert validation, limited trials, revision, and implementation. The research participants include school counselors, students, and school administrators. Data are collected through observation, interviews, questionnaires, and documentation and are analyzed using qualitative and quantitative methods. The expected outputs include an applicable and systematic comprehensive guidance and counseling program model, an implementation guide, and improved quality of school counseling services.